Effect of a 3-week program of cane training and use on gait of individuals with Parkinson’s disease: Protocol for a randomized controlled trial - Jordana de Paula Magalhães; Merrill R. Landers; Aline Alvim Scianni; Maria Eduarda Bueno Santos Ribeiro; Christina Danielli Coelho de Morais Faria (PLoS ONE, 2026)
Introduction Although studies examining the immediate effects of cane use in individuals with Parkinson’s disease (PD) have reported negative outcomes, the efficacy and safety of structured training programs for assistive device use remain to be investigated. Furthermore, the limited evidence regarding patient-reported outcomes hinders the implementation of patient-centered, evidence-based practices in prescribing assistive devices for this population. Objective To investigate the effect of cane training and use on gait speed (primary outcome), gait confidence, cadence, step length, functional mobility, freezing of gait, fear of falls, and satisfaction with the use of a cane (secondary outcomes) in individuals with PD. Materials and methods A double-blind, randomized controlled trial will be carried out. A total of 26 individuals with PD will be randomly divided into two groups: (1) cane training and use (experimental group) or (2) global stretches and health education (time and attention controlled group). The intervention will be provided in four sessions lasting 40 minutes each, spaced over 15 to 22 days. Individuals will be instructed to use a cane (experimental group) or perform stretching exercises (time and attention-controlled group) daily, starting from the first day of training. Assessments will be conducted at the beginning of the study (week 0), post-intervention (week 3, post-intervention), and one month after the cessation of the intervention (week 8, follow-up). The primary outcome is gait speed. Secondary outcomes include gait confidence, cadence and step length, freezing of gait, functional mobility, fear of falls, and satisfaction with the use of cane. Between-group differences will be measured using a two-way repeated measures ANOVA, following intention-to-treat and per-protocol approaches (α=0.05), Discussion The results of this study may improve the prescription of canes for individuals with PD. If effective, the cane could serve as a simple, low-cost, evidence-based intervention, and the training protocol could be replicated in clinical practice. Clinical trial registration Effect of Training and Use of Cane on Gait in Individuals With Parkinson’s Disease - NCT06950255.